ANALISA HUBUNGAN KEKAYAAN BERSIH WAJIB PAJAK BADAN DENGAN BEBAN PAJAK PENGHASILAN PADA KANTOR PELAYANAN PAJAK PRATAMA PALEMBANG ILIR TIMUR - Sonang PestariaP (Fakultas Ekonomi Universitas Tridinanti Palembang, 2012)
ABSTRACTThis research is about finding the correlation of taxpayerÃ¢â‚¬â„¢s net worth with income tax expense at Small Taxpayers Office located at Ilir Timur, Palembang.Variables used for this are independent variable of Net Worth Tax Payers (X) and dependant variable of Income Tax Expense (Y).The purpose of this research is to understand the relationship between the tax agency obligation in correlation with income tax expense and how these two variables effects each other. Analytical descriptive method will be used in this research.After thorough feasibility test for data input, result is achieved after analyzing data with simple linear regression analysis, correlation analysis, and R-Square and T-Test analysis. Result is as followed.There is a positive relation between net worth and income tax expense with correlation coefficient of 0,568. This coefficient is reaching the strong level of correlation based on interpretation of correlation table. Correlation coefficient signed positive (+), means that net worth is proportional to income tax expense that makes any increase for net worth will cause an increase for income tax expense. R-Square analysis gives how much the impact of X for every variation of Y. R-Square of 0.323 refers for 32.30% of total variation of Y is affected by X, while the rest of 67.70% is affected by other factors.Ã‚Â The linear equation resulted is Y = 547911276.770118 + 0.025747X, refering that every 1 coefficient of net worth of taxpayer will affect approximately 0,02574 or 2,57% of income tax expense. From the T-Test analysis resulted that ttest > ttableÃ‚Â or 3.52 > 1.706, give rise to Alternative Hypothesis (Ha) to be accepted while Null Hypothesis (H0) to be rejected. This conclude that net worth is significantly affects the income tax expenseKey word : taxpayerÃ¢â‚¬â„¢s net worth, income tax expense.